2001
DOI: 10.1161/hc4901.100526
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Gene Expression in Fetal and Failing Human Heart

Abstract: Background-Previous studies suggest that the failing heart reactivates fetal genes and reverts to a fetal pattern of energy substrate metabolism. We tested this hypothesis by examining metabolic gene expression profiles in the fetal, nonfailing, and failing human heart. Methods and Results-Human left ventricular tissue (apex) was obtained from 9 fetal, 10 nonfailing, and 10 failing adult hearts. Using quantitative reverse transcription-polymerase chain reaction, we measured transcript levels of atrial natriure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

38
411
4
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 541 publications
(458 citation statements)
references
References 47 publications
38
411
4
5
Order By: Relevance
“…This would also be consistent with findings in the failing heart where function can be improved by treatment with FA oxidation inhibitors (45). The failing heart has limited capability to oxidize FA because it has reverted to a fetal metabolic gene profile and depends on glucose utilization for energy (46,47).…”
Section: Discussionsupporting
confidence: 83%
“…This would also be consistent with findings in the failing heart where function can be improved by treatment with FA oxidation inhibitors (45). The failing heart has limited capability to oxidize FA because it has reverted to a fetal metabolic gene profile and depends on glucose utilization for energy (46,47).…”
Section: Discussionsupporting
confidence: 83%
“…We found a profound reduction of Tfam transcripts (Table 2) confirming efficient disruption of the Tfam gene in knockout hearts. We found reduced expression of sarcoplasmic reticulum Ca 2ϩ ATPase (Serca2) and increased expression of atrial natriuretic factor (Anf) mRNA (data not shown) consistent with our previous results (14) and observations in other heart failure models (26)(27)(28). Several changes in gene expression were compatible with compensation of impaired mitochondrial function, e.g., genes involved in import, synthesis, and turnover of mitochondrial proteins showed increased expression in MS and LS knockouts ( Table 2).…”
Section: Major Alterations In Gene Expression Occur Concomitant With supporting
confidence: 90%
“…13 Moreover, an extensive body of experimental studies has revealed altered expression of metabolic genes, proteins and metabolites that contribute to cardiovascular disease (CVD), including ischemia-reperfusion injury, cardiac remodeling and heart failure. 8,14 The ability to probe alterations in cardiac energetics non-invasively, and in real time, may improve our understanding of the pathogenesis of CVD and improve patient care.…”
mentioning
confidence: 99%